Effect of denture cleansing agents on tensile and shear bond strengths of soft liners to acrylic denture base - Farhang Mahboub; Fariba Salehsaber; Fereydoon Parnia; Vahedeh Gharekhani; Yousef Kananizadeh; Mahsa Taghizadeh (Tabriz University of Medical Sciences, 2017)
Background. The aim of the present study was to evaluate the effect of Corega and 2.5% sodium hypochlorite cleansing agents on the shear and tensile bond strengths of GC soft liner to denture base. Methods. A total of 144 samples (72 samples for tensile and 72 for shear bond strength evaluations) were prepared. The samples in each group were subdivided into three subgroups in terms of the cleansing agent used (2.5% sodium hypochlorite, Corega and distilled water [control group]). All the samples were stored in distilled water, during which each sample was immersed for 15 minutes daily in sodium hypochlorite or Corega solutions. After 20 days the tensile and shear bond strengths were determined using a universal testing machine. In addition, a stereomicroscope was used to evaluate fracture modes. Data were analyzed with one-way ANOVA, using SPSS 16. Results. The results of post hoc Tukey tests showed significant differences in the mean tensile and shear bond strength values between the sodium hypochlorite group with Corega and control groups (P=0.001 for comparison of tensile bond strengths between the sodium hypochlorite and control groups, and P<0.001 for the comparison of tensile bond strengths between the sodium hypochlorite and Corega groups and the shear bond strengths between the sodium hypochlorite and Corega groups, and sodium hypochlorite and control groups).The majority of failures were cohesive in the control and Corega groups and cohesive/adhesive in the sodium hypochlorite group. Conclusion. Immersion of soft liners in Corega will result in longevity of soft liners compared to immersion in sodium hypochlorite solution and sodium hypochlorite solution significantly decreased the tensile and shear bond strengths compared to the control and Corega groups.